The Evaluatıon Of The Changes Occurıng In The Vertıcal Dırectıon Of The Face In Cases Treated Wıth Actıvator + Occıpıtal Headgear Combınatıon - Zahir Altuğ; Zehra Bayazıt; Haluk İşeri; Hakan Gögen (Galenos Yayinevi, 1989)
The aim of this study was to evaluate the vertical skeletal and dentoalveolar changes in the Class II Division 1 cases treated with the activator + occipital headgear combination. The present study was performed on 40 subjects and comprised 20 subjects who had undergone activator + occipital headgear therapy and 20 control subjects who had received no orthodontic treatment. 15 linear and angular measurements were performed on 80 lateral cephalometric films of 40 subjects. By comparing the treatment and control groups, the changes related to growth was eliminated and following results were obtained: SNA and ANB angles were reduced in treatment group (p < 0.01) and the difference between treatment and control groups were statistically significant (p < 0.01). Jarabak ratio did not show any change in the treatment group but decreased in the control group (p < 0.05) and the difference between treatment and control groups was statistically significant (p < 0.05). The growth of lower anterior alveolar height was inhibited by treatment when compared to control group (p < 0.01).